0333 A Novel Rat Model of Obstructive Sleep Apnea. (27th April 2018) - Wu, H; Zhang, H; Lv, Q; Qin, Y; Fang, F; Wei, Y
Abstract: Introduction: Animal models of obstructive sleep apnea (OSA) have not yet satisfied been developed (e.g., chronic intermittent hypoxia model; artificial airway stenosis model) with respective limitations. Thus, it is necessary to find a new method that can better simulate the main characteristics and process of OSA, i.e., chronic intermittent hypoxia with concurrent respiratory efforts, and can be utilized at scale. Methods: We utilized a rat model by constructing a molding device consisting of a body container, head cover, air bag, piston and controller. When the air bags are inflated, the space between the body container and head cover is constricted. A vent for the rat's nostrils in the head cover allows air flow. The controller and piston opens and closes the vent. To testify this device, six Wistar rats were sedated and put into the device to cause apnea (60s), during spontaneous breathing (90s) under anesthesia for 3 hours/day for 4 weeks. Tail blood oxygen saturation and diaphragmatic muscle electromyography (EMGdi) were monitored. After 4 weeks, blood pressure and vasodilatation were measured. We compared results with six rats who underwent sham control procedures. Results: Rats exposed to the device demonstrated regular intermittent hypoxemia and concurrent respiratory efforts by EMGdi. After 4 weeks, these rats had higher systolic blood pressure (129.1 ± 3.0 vs. 111.6 ± 8.4 mmHg, p<0.001), mean blood pressure (100.9 ± 6.3 vs. 85.7 ± 8.1 mmHg, p<0.001) and diastolic blood pressure (88.3 ± 6.6 vs. 72.4 ± 11.3 mmHg, p=0.001) compared with controls. Impaired endothelium-dependent relaxation was found in rats with apnea. Conclusion: This new rat model of OSA recapitulates the key physiologic aspects of OSA, including cardiovascular sequelae such as hypertension and endothelial dysfunction. This facile device may be useful in the study of OSA. Support (If Any): This study was supported by NSFC (Project 81470567), Beijing Medical Project 2016-4, the Beijing Key Laboratory of Upper Airway Dysfunction and Related Cardiovascular Diseases (NO: BZ0377) and the Beijing Municipal Administration of Hospitals Clinical Medicine Development of Special Funding Support (ZYLX201605).